Hubungan Antara Sense Of Humor Dan Intimate Friendship - Riska, Novia; Widyastuti, Ami (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2019)
Humans as social beings cannot escape from others. This makes humans need to interact with people around. One form of interaction is by making friends. Friendship is considered related to mutual understanding and sharing of thoughts, feelings and other secrets. One factor that determines the quality of friendships is the closeness or intimacy. Sense of humor is one of the factors that support the formation of closeness. This study aims to determine the relationship between sense of humor with intimate friendship. The research sample was 394 students of UIN Suska Riau, who were determined using proportional nonrandom sampling technique. Measuring instruments use a scale of sense of humor (Thorson & Powell, 1993) and intimate friendship scale (Sharabany, 2008). The research hypothesis is